(untitled) (KULT_online, 2013)
Overbeck’s analysis of social utopias written by 19th century American women provides an innovative, detailed, and broadly contextualized perspective on the discourse systems "gender" and "education". Overbeck puts her focus on strategies of transvaluating discursive terms, presenting a dialogic thesis, which interacts with the readers, sources, and the state of research in multiple ways. From a historiographic perspective, it remains to be seen whether the source material provided allows for implications on dominant discursive strategies to be drawn and to what extent the precise examples of analysis and the theoretical considerations can provide evidence for Overbeck’s main hypothesis – the hypothesis that the transvaluation of gender-norms and educational ideas in literary utopias opens up public discourse for new ideas enabling "real progress" in the broad field of female education.